The Effect of Work Stress and the Work Environment on the Performance of Female Teachers, with Cyberloafing as a Mediating Variable, at Public Elementary Schools in the Sungai Kunjang Subdistrict - Ivni Alfrisqa Mustafa; Nurlaili Nurlaili; Haeruddin Haeruddin; Masrur Yahya; Widyatmike Gede Mulawarman; Sudarman Sudarman (Journal of Educational Sciences, 2026)
Female teachers face increasing demands from instructional responsibilities, administrative tasks, work pressure, and digital technology use. This study examined the effects of work stress and work environment on female teacher performance, with cyberloafing as a mediating variable. A quantitative explanatory design was employed involving 210 female teachers from public elementary schools in Sungai Kunjang District. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics, regression, path analysis, the Sobel test, and bootstrapping. The findings showed that work stress negatively affected cyberloafing and teacher performance, while the work environment positively influenced teacher performance but had no significant effect on cyberloafing. Cyberloafing positively affected teacher performance and partially mediated the relationship between work stress and performance, indicating that moderate personal internet use may provide brief recovery periods that support productivity. However, cyberloafing did not mediate the relationship between the work environment and performance. Overall, work stress, work environment, and cyberloafing help explain female teacher performance. The findings emphasize managing workplace stress, fostering supportive environments, and viewing limited cyberloafing as a controlled coping strategy rather than excessive personal internet use.